The Delft Prototype Laboratory - M. Eekhout (Research in Design Series, 2016)
The Prototype Laboratory initiated and maintained by the Chair of Product Development at the Faculty of Architecture, TU Delft, has set an example in architectural education for hands-on 'learning-by-making' for students. According to the authors of this book, in the current curriculums time spent on practical work is not rewarded and students are educated in an abstract concept of architecture, not getting a proper feeling for materialization. A semester of designing, engineering, producing and building a prototype with their own hands after their own design often gives students a boost in their education. The Delft Prototype laboratory was the base of around 1,000 students, now professionals. Some architect's offices make prototypes regularly as their designs are quite experimental and require more insight for the designing architect, before the realization of his building. Prototypes of technical components are often developed parallel to the building process. The Prototype Laboratory at the Faculty of Architecture was supervised for almost 18 years by Peter van Swieten. He describes his experiences in this book, in collaboration with the initiator, professor Mick Eekhout. Marcel Bilow took over the Bucky Lab, as it is called, from 2012 onwards.